PERAN GAYA HIDUP TERKAIT MAKANAN DALAM MEMPREDIKSI NIAT MAHASISWA UNTUK MENGURANGI KONSUMSI DAGING - Nurcahyaning Tyas, Putri Reygina; Setiawan, Budi; Hartono, Rachman (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
The increasing global meat consumption poses significant environmental challenges, including greenhouse gas emissions, land degradation, and excessive water usage, necessitating a shift toward sustainable dietary habits. The aim of this study is to investigate university students' intentions to reduce meat consumption, focusing on the influence of food-related lifestyle, attitude toward meat reduction and socio-demographic factors. Data collected from 397 students were analyzed using hierarchical cluster analysis using the ward method, anova, pearson correlation, and multiple linear regression. Five consumer clusters were identified such as rational, adventurous, careless, conservative, and uninvolved, each showing distinct consumption patterns. The Adventurous cluster exhibited the highest intention to reduce meat consumption, driven by novelty-seeking and openness to new culinary experiences. Attitude emerged as the most influential predictor of intention, surpassing gender and lifestyle clusters, with women demonstrating stronger intentions than men. By analyzing these dynamics, the study provide insights for targeted strategies, including educational campaigns, product innovations, and policies supporting meat reduction consumption